1966
DOI: 10.1007/bf01268186
|View full text |Cite
|
Sign up to set email alerts
|

Ver�nderungen des Gehaltes der freien Fetts�uren und der Ketonk�rper im Blut alloxandiabetischer Ratten nach i.v. Fettbelastung und Heparinapplikation

Abstract: Changes in the serum levels of free .fatty acids and ketone bodies in aIloxan-diabetie rats after intravenous loading with fat and application of heparin.Summary. Fat, with and without simultaneous heparin has been given intravenously to normal and to chronic alloxan-diabetic rats. The concentration of free fatty acids and ketone bodies in the blood was determined a~ several intervals after the injection. Although after the i.v. administration of fat the profile of the FFA-elevation in serum was parallel in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

1967
1967
1969
1969

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
0
0
1
Order By: Relevance
“…This may be due to the lipolytic properties of caffeine and the increased supply of fatty acids to the liver. This assumption is in accordance with the find ings of Baumung et al [2], who observed a further increase of ketone bodies in the serum of alloxan diabetic mice when the concentration of FFA was further raised by means of fat ingestion and administration of heparin.…”
Section: Ketone Bodiessupporting
confidence: 81%
“…This may be due to the lipolytic properties of caffeine and the increased supply of fatty acids to the liver. This assumption is in accordance with the find ings of Baumung et al [2], who observed a further increase of ketone bodies in the serum of alloxan diabetic mice when the concentration of FFA was further raised by means of fat ingestion and administration of heparin.…”
Section: Ketone Bodiessupporting
confidence: 81%
“…Injektion von «Intralipid» bei chronisch alloxandiabetischen Ratten einen niedrigeren Gehalt an freien Fettsäuren im Serum (SeFFA) gefunden als bei stoffwechsel gesunden Kontrollieren (1).…”
unclassified